Parasite assemblages in volatile host stocks: inter- and intra-cohort variability restrict their value as biological tags for squid stock assessment - Gutierrez, Maria Paz (2023)
The Argentine shortfin squid, Illex argentinus, inhabits in the southwest Atlantic; it is a semelparous species which grows rapidly along its one year lifespan. The identification of its stocks is critical for sustainable fishery exploitation. Parasites have been used as biological indicators in a lower number of studies dealing with squids, therefore a validation of this methodology is necessary. The intra- and inter-cohort variability of parasite assemblages in the summer-spawning stock (SSS) of I. argentinus was analyzed to assess their value as indicators of stock structure. Four squids samples from the continental shelf of central Patagonia, corresponding to three consecutive cohorts, were examined for metazoan parasites. Results evidenced heterogeneity in terms of parasite assemblages composition and structure, dominated by short-lived gastrointestinal parasites, with a strong influence of host size, but no effect of squid sex. These changes are related to their recent habitats and diets, which change with ontogeny and migrations, clouding any interpretation of patterns when samples spatially or temporally separated are compared. Many squid species share these characteristics; therefore, it is recommended that the use of parasites as biological tags should be restricted to simultaneous sampling, while size or age must be considered for deriving proper conclusions.